Can a light-touch graduation model enhance livelihood outcomes? Evidence from Ethiopia - Leight, Jessica; Alderman, Harold; Gilligan, Daniel O.; Hidrobo, Melissa; Mulford, Michael (International Food Policy Research Institute, 2023)
In recent years, a growing literature has examined the potential of multifaceted, intensive “graduation model” interventions that simultaneously address multiple barriers constraining households’ exit from poverty. In this paper, we present new evidence from a randomized trial of a lighter-touch graduation model implemented in rural Ethiopia. The primary experimental arms are a bundled intervention including a productive transfer valued at $374 (randomly assigned to be cash or an equivalent value in poultry), training, and savings groups; a simpler intervention including training and savings groups only; and a control arm. We find that three years post-baseline, the intervention inclusive of the transfer leads to some increases in assets, savings, and cash income from livestock, though there is no shift in consumption or household food security; these effects are consistent regardless of the modality of the transfer (cash versus poultry). The effects of training and savings groups alone are minimal.